GREENHOUSE GASES : ITS SOURCES AND EMISSION FROM DIFFERENT COUNTRIES - Upadhyaya, Bhawana (Innovare Journal of Sciences, 2016)
Abstract: In this research paper, researcher will heed the different sources of GHG's and only on CO2 emission from different countries because among the GHG's, carbon dioxide is the most dominant gas causing global warming which accounts for nearly 77% of global total CO2 equivalent greenhouse gas (GHG) emissions (IPCC 2007c). Concentration of (GHG's) in the atmosphere has increased rapidly due to anthropogenic activities resulting in significant increase in the temperature of the earth. Increase in the concentration of these greenhouse gases results in global warming. The increasing interest in quantification of greenhouse gas emissions comes as a result of growing public awareness of global warming. Many countries and organizations are estimating their greenhouse gas emissions and developing strategies to reduce their emissions. As per Intergovernmental Panel on Climate Change (IPCC), carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O), hydro fluorocarbons (HFCs), per fluorocarbons (PFCs) and sulfur hexafluoride (SF6) are the major greenhouse gases. Descriptive survey method was used for collecting the data. The result shows that the different sources of GHG's emission are Natural and human sources and the biggest CO2 emitter was China in 2013.